Development of an adaptive façade for visual comfort, daylight and thermal control element - Liang, Runqi (2018)
Thermochromic (TC) windows were developed as a passive building component to improve indoor comfort and building energy conservation in place of traditional clear glazing systems. TC materials enable a spectrum-dependent regulation of solar radiation through windows stimulated by heat. When the temperature is higher than its transition temperature, less solar radiation, primarily in the near infra-red (NIR), will be admitted inside the building, reducing over-heating on hot days. Meanwhile, the TC materials tint to bluish or brownish appearance along with the transition. Most research about the commonly studied Vanadium dioxide (VO2) based TC windows was focused on fabrication methods and properties improvement of VO2 based materials, and a few numbers of studies investigated their energy performance when applied in buildings. Therefore, this research conducted a thorough investigation of TC windows applied in buildings, covering characteristic of TC windows, energy efficient, daylighting performance, and human response affected by different types of TC windows. Both simulation and experimental methods were carried out to explore the potential of TC windows. That aim is to provide a detailed guidance for the development of TC materials that are more flexible and acceptable to use in a practical building. The comprehensive analysis mainly consists of four parts: 1) simulation work on the evaluation of TC windows on energy efficient and daylighting, also the window size effects under five typical climates; 2) further evaluation of the potential of developed TC windows with enhanced capability of adjusting visible and NIR transmittance individually or cooperatively; 3) experimental investigation of the research hypothesis that TC tinted window has no effect on the human visual performance and subjective sensation, in a test room cubicle with a low level of simulated daylit (100lux); 4) further experimental investigation to detect the acceptance range of tinting for different windows at an indoor comfort illuminance level (350 lux). Findings show that compared with reducing the transition temperatures, improving capability of adjusting visible or NIR transmittance is more effective to improve both daylighting and energy performance. TC windows are more energy efficient when applied in buildings with large glazing area under cooling dominated climates. However, dynamic reduction of visible transmittance is required to decrease the risk of visual discomfort caused by over daylighting, especially for cities with lower solar altitude. Under a dark illuminance, bronze tinted TC windows were preferred subjectively, however, subjects had better visual performance under blue tinted TC window conditions. Sustained attention (i.e., focus on an activity for a long period of time) was not affected by TC window conditions (i.e., with correlated colour temperature (CCT) ranging from 3300 to 11000K), but further tinted bronze window was subjectively considered to improve concentration. Therefore, adjustment of visible transmittance is highly recommended for warm tinted TC windows. Simulation and lab experiment might have some limitation on this study, further work is suggested by carrying out further validation and employing more samples.